Analisis Efektivitas Pengolahan Data Bongkar Muat guna Pelaporan pada Aplikasi Sirani di KSOP III Tanjung Pakis - Asrul Muhamad Nashr; Faris Nofandi; Eka Nurmala Sari Agustina; Muhammad Dahri (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Ports are critical infrastructure in maritime transportation, facilitating the movement of goods and people while serving as hubs for economic activities. The Tanjung Pakis Class III Harbormaster and Port Authority Office (KSOP) utilizes the Electronic Reporting Information (SIRANI) application for reporting loading and unloading data. However, challenges such as discrepancies, technical disruptions, and delays in data processing often arise. This study aims to describe the loading and unloading data processing and the efficiency of reporting time on the SIRANI application at KSOP Class III Tanjung Pakis. Employing a descriptive qualitative approach through interviews, observations, and documentation, the research finds that data processing is less effective due to low data validity and errors in the Inaportnet platform. Reporting to SIRANI is also inefficient due to delays in data handling and technical issues with the application. Corrective measures, such as early data verification and manual data handling by reporting officers, have improved effectiveness by reducing the process from five to three steps and cutting reporting time from 6 hours to 3 hours and 30 minutes. The study concludes that optimizing data processing and inter-unit coordination can enhance the effectiveness and efficiency of reporting. Recommendations for future research include real-time integration and the development of backup mechanisms to address technical disruptions.